THE RELATIONSHIP BETWEEN ONLINE GAME ADDICTION WITH STUDENT LEARNING MOTIVATION AT SMPI MIFTAHUL JANNAH AND MTS NAHDLATUL NASYIIN IV PASANGGAR PEGANTENAN PAMEKASAN - Zatihulwani, Eliza Zihni; Habiburrohman; Setiawan, Roni; Puspita, Sylvie (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
Background: Rapid technological advances can change various aspects of everyday life, such as online gaming. Playing online games can foster curiosity and attract interest, and can even cause addiction that interferes with learning motivation. Objectives: This research aims to understand the correlation between addiction to playing online games and students' learning motivation at SMPI Miftahul Jannah and MTS Nahdlatul Nasyiin IV Pasanggar Pegantenan Pamekasan. Design: This research adopted a quantitative approach with correlational analysis methods and cross-sectional research, involving 60 students from SMPI Miftahul Jannah and MTS Nahdlatul Nasyiin IV using purposive sampling techniques. The data collection tool consists of questionnaires and data analysis is conducted using Spearman's rank correlation test. Results: This research found that the majority of respondents were addicted to playing online games at a high level, namely 37 respondents (61.7%). Meanwhile, most respondents had low-level learning motivation, and 37 respondents (61.7%). From the results of the Spearman Rank Test, a significant value of 0.000 (p < 0.05) was found with a correlation coefficient of -0.666, indicating a strong negative relationship between Addiction to Playing Online Games and Learning Motivation in students at SMPI Miftahul Jannah and MTS Nahdlatul Nasyiin IV in Pasangggar Pegantenan Pamekasan. Conclusion: Time management, schedules, supervision, family support, and healthy substitute activities are needed as a solution.